Inorganic fertilizer consumption in SADC region in the context of the Malabo declaration : sub-regional analysis - Makhura, Moraka N. (University of Pretoria, 2025)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2024.